WATER SPREAD TEST ON IOT (Internet of Things) BASED AUTOMATIC IRRIGATION SYSTEM - Eko Noerhayati; Anita Rahmawati; Satriyo Yoga Wahyudi (Universitas Islam Malang, 2020)
This research is intended to determine the performance of the tools in the sprinkler irrigation system using controls (android). This activity was carried out in an experimental garden in the laboratory Enviro-Hydro of the Civil Engineering Faculty of Engineering, University of Islamic Malang, covering an area of 80 m². There are two variables used as a reference for sprinkler performance, namely automatic and manual with each valve opening 45°-90°, on 4 sprinklers installed on the land with a distance of 1 m each other. Water flows from 2 tadons that are placed parallel. The method used to analyze the data using the T test which compares the observation results of water distribution from automatic and manual sprinkler openings. The results of measuring the distribution of automatic and manual sprinkler water show that the results are not much different, only a difference of 1% so that the performance of both automatic and manual sprinklers has not different results.